Casting Ugliness: Redefining Aesthetics in Mulk Raj Anand’s Untouchable - Dhungel , Nabaraj (Journal of Innovation in Academia, 2025)
This article explores how Mulk Raj Anand, through Untouchable, redefines the aesthetics of beauty and ugliness by challenging caste-based hierarchies in 1930s colonial India. Anand critiques the idealization of upper-caste purity by exposing the moral decay of Brahmins and Chhetris, while attributing ethical and humanitarian beauty to untouchables like Bakha, who embody honesty, humility, and labor worship. Employing Bakhtin’s concept of grotesque realism, Mukarovsky’s idea of socially constructed beauty, and Raymond Williams’ critique of aesthetic idealization, the study frames Anand’s politics of aesthetics within the discourse of social justice. It also draws on B.R. Ambedkar’s Annihilation of Caste to contextualize the novel’s anti-caste ideology. Anand ultimately destabilizes binary notions of beauty and grotesqueness, portraying the oppressed as morally beautiful and the so-called pure as ethically corrupt. The novel becomes a powerful critique of caste orthodoxy and a celebration of the dignity and humanity of the marginalized.